Discussion boards as tools in blended efl learning programs (2009)
This paper reports on a study conducted at Universidad Nacional de Colombia in the ALEX Virtual English program. It shows the main characteristics of discussion boards when used as a main activity in an EFL blended course. The study took place in the second semester of 2008 when the program was in the piloting stage and it illustrates the importance of the discussion board tool in the transition from face-to-face education to virtual education. The research followed the qualitative principles and shows the use given to discussion boards by some of the students of the program. Students’ perceptions of the tool are registered as a description to give the reader the opportunity to develop her/his own perception on its use. Key words: Discussion boards, ALEX Virtual English program, autonomy, blended modality, teachers’ accompaniment Este artículo reseña un estudio realizado en la Universidad Nacional de Colombia en el programa ALEX Virtual – inglés. Se muestran algunas características de los foros de discusión como actividad principal en un curso mixto (presencial y virtual) de inglés como lengua extranjera. El estudio se realizó en el segundo semestre del 2008, cuando el programa aún estaba en fase de pilotaje y ejemplifica la importancia de los foros de discusión en la transición de la modalidad presencial a virtual. La investigación siguió los principios cualitativos y muestra el uso que dan algunos estudiantes del programa a los foros de discusión. Se describen las percepciones de los estudiantes sobre la herramienta para que el lector pueda desarrollar su propio punto de vista sobre el uso de esta. Palabras clave: Foros de discusión, programa ALEX Virtual – inglés, autonomía, modalidad mixta, acompañamiento del profesor